(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article examines professional training as a condition for career growth of employees of the security service of Ukraine. The achievements of scientists in determining the types of professional training are considered. The norms of legislation regarding the professional training of employees are considered. The impact of professional training on a career in the Security Service of Ukraine has been studied. Author’s definitions of the concepts: "initial professional training of employees", "retraining of employees", "advancing the qualifications of employees" have been proposed. It has been proven that in order to increase the motivation of employees of the Security Service of Ukraine to study and perform their duties efficiently, it is advisable to more closely link success in studies and official activities to the career growth of employees. There is also a need to actually ensure continuous education of employees of the Security Service of Ukraine, the practical orientation of professional training, and the timely introduction of best practices in counterintelligence and operational-search activities into the educational process. In addition, the professional training of employees of the Security Service of Ukraine requires the introduction of the best achievements of European science and education into the educational process.